Advancing digital health applications: priorities for innovation in real-world evidence generation - Stern, Ariel Dora; Brönneke, Jan; Debatin, Jörg F; Hagen, Julia; Matthies, Henrik; Patel, Smit; Clay, Ieuan; Eskofier, Bjoern; Herr, Annika; Hoeller, Kurt; Jaksa, Ashley; Kramer, Daniel B; et al. (The lancet. Digital health, 2022)
In 2019, Germany passed the Digital Healthcare Act, which, among other things, created a “Fast-Track” regulatory and reimbursement pathway for digital health applications in the German market. The pathway explicitly provides for flexibility in how researchers can present evidence for new digital products, including the use of real-world data and real-world evidence. Against this backdrop, the Digital Medicine Society and the Health Innovation Hub of the German Federal Ministry of Health convened a set of roundtable discussions to bring together international experts in evidence generation for digital medicine products. This Viewpoint highlights findings from these discussions with the aims of (1) accelerating and stimulating innovative approaches to digital medical product evaluation, and (2) promoting international harmonisation of best evidentiary practices. Advancing these topics and fostering international agreement on evaluation approaches will be vital to the safe, effective, and evidence-based deployment and acceptance of digital health applications globally.